THE EFFECT OF WHOLESOME SCATTERING GAME ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABILITY (A Study at the Eight Grade of SMP NEGERI 1 Angkola Selatan in 2018/2019 Academic Year - Nirwana Wulan Dari (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The purpose of this research are to find out: 1) the extent of the application of wholesome scattering game on students’ writing descriptive text at the eighth grade of SMP N 1 Angkola Selatan. 2)The extent of the students’ ability in writing descriptive text before and after using wholesome scattering game at the eighth grade of SMP N 1 Angkola Selatan. 3) Whether there is any significant effect of wholesome scattering game on students’ writing descriptive text at the eighth grade of SMP N 1 Angkola Selatan. The population of this research is all of the eight grade Students of SMP N 1 Angkola Selatan consists of 100 students. The sample was 27 students which are taken by purposive sampling. The research method is used by experimental method. Then the data is collected by using the instrument. The instrument used is composition writing test. The hypothesis of this research is there is significant effect of wholesome scattering game on students’ writing descriptive text ability at the eighth grade of SMP N 1 Angkola Selatan. The calculation of ttest formula is higher than score of ttable. The score of the ttest is 2.53 meanwhile the score of ttable is 2.06 at 5% significant level with (df) 27, (ttest 2.53 > ttable 2.06) and hypothesis is accepted. It means that there is a significant effect of wholesome scattering game on students’ writing descriptive text ability at the eighth grade of SMP N 1 Angkola Selatan.